METHODOLOGICAL FOUNDATIONS FOR ENSURING SOCIAL JUSTICE IN THE CONTEXT OF CONTEMPORARY UZBEKISTAN - Ne’matilloyevich, Makhmudov Izzatillo (PT. Antis International Publisher, 2025)
Objective: This article examines the theoretical and methodological foundations of social justice in the context of New Uzbekistan, highlighting its significance for sustainable development and the creation of a just society. Method: The study adopts a comprehensive, interdisciplinary approach, integrating systemic, comparative-philosophical, hermeneutic, semiotic, historical-genetic, axiological, institutional, and political-legal frameworks. These methodologies are applied to understand the complexity of social justice as both a theoretical concept and a practical system within the legal, political, economic, and spiritual domains. Results: The analysis reveals that social justice in New Uzbekistan is deeply interconnected with national values, civilizational identity, and the functioning of key institutions. It underscores the importance of integrating these elements to achieve a balanced and equitable society. Novelty: The novelty of this research lies in its multidisciplinary perspective, which combines both theoretical and practical approaches to studying social justice in the unique sociocultural and political context of Uzbekistan. This approach offers new insights into the role of social justice in shaping the country’s sustainable future.